High-hydrophobicity polyacrylonitrile spinning solution and preparation method thereof
By copolymerizing fluorine-containing monomers and alkenyl silanes in the polyacrylonitrile spinning stock solution, the problem of insufficient stability and hydrophobic ability of the fiber material is solved, and efficient oil-water separation and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411914673.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing polyacrylonitrile spinning stock solution has shortcomings in terms of stability and hydrophobic capacity, which limits its application in the field of oil-water separation.
By copolymerizing fluorogenic monomers and alkenyl silanes in polyacrylonitrile, a highly hydrophobic polyacrylonitrile spinning stock solution was prepared, and the hydrophobic ability and chemical stability of the fiber material were improved by using the structure of fluorogenic monomers and alkenyl silanes.
It significantly improves the stability and hydrophobic ability of fiber materials, making them have wide application potential in the field of oil-water separation, and at the same time has excellent mechanical properties and weather resistance.
Smart Images

Figure CN119798532A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a highly hydrophobic polyacrylonitrile spinning solution and a preparation method thereof. Background Art
[0002] The advent of high-performance carbon fiber marks another breakthrough in the history of material development. It has excellent properties such as high specific strength, high specific modulus, ablation resistance, wear resistance, and fatigue resistance. As the most important reinforcing material in the field of advanced composite materials, it is widely used in various fields such as military and civilian industries. Compared with viscose-based and asphalt-based carbon fibers, polyacrylonitrile-based carbon fibers have been vigorously developed due to their simple production process and good product mechanical properties, becoming the main direction of carbon fiber development.
[0003] Polyacrylonitrile-based carbon fiber is a new material that developed rapidly in the 1960s. It is widely used in military industries such as satellites, launch vehicles, tactical missiles, and spacecraft because of its light weight, high specific strength, high specific modulus, high temperature resistance, corrosion resistance, wear resistance, fatigue resistance, electrical conductivity, and thermal conductivity. It has become an indispensable material in the aerospace industry. Excellent carbon fiber precursor should have the characteristics of high heat resistance, less pore structure, less surface defects, dense structure, and good tensile properties.
[0004] Polyacrylonitrile-based carbon fiber is made of a polymer with acrylonitrile as the main chain structural unit, which is spun and then oxidized and carbonized. The synthesis of acrylonitrile copolymer is the first step in preparing precursor. The quality of polyacrylonitrile precursor is not only affected by the spinning process conditions, but more importantly by the microstructure of the polymer molecular chain, such as the type of comonomer, the composition of the comonomer, the molecular weight and the molecular weight distribution, etc. Therefore, high-quality polyacrylonitrile polymer is the prerequisite for preparing high-quality precursor.
[0005] The spinning solution used to prepare polyacrylonitrile precursor is divided into homopolymer and copolymer. The solubility of acrylonitrile homopolymer is poor, which makes the spinnability poor. In addition, due to the presence of a large number of -CN groups in its chemical structure, the interaction between macromolecules is strong, and there is no side chain, which results in a long pre-oxidation and carbonization cycle, resulting in high product cost and low strength. In order to overcome the above shortcomings of homopolymer polyacrylonitrile resin, the resin is usually modified by adding binary or multi-component vinyl comonomers to acrylonitrile.
[0006] However, the stability of fiber materials made from polyacrylonitrile spinning solution in the prior art still needs to be improved, and they do not have high hydrophobicity, which limits their application in the field of oil-water separation.
[0007] Therefore, there is an urgent need for a polyacrylonitrile spinning solution that can significantly improve the stability and hydrophobicity of fiber materials. Summary of the invention
[0008] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide a highly hydrophobic polyacrylonitrile spinning solution and a preparation method thereof which can significantly improve the stability and hydrophobicity of fiber materials.
[0009] Technical solution:
[0010] A highly hydrophobic polyacrylonitrile spinning stock solution, wherein the highly hydrophobic polyacrylonitrile spinning stock solution is prepared by copolymerizing acrylonitrile, a fluorine-containing monomer and alkenyl silane in an organic solution;
[0011] The fluorine-containing monomer has a structure as shown in the following formula A:
[0012]
[0013] The highly hydrophobic polyacrylonitrile spinning stock solution of the present invention has a polyacrylonitrile structure with good processability, and can form a fiber material with good mechanical properties and weather resistance after spinning. It can not only replace wool as a textile, but also be made into a fiber membrane as a membrane material for oil-water separation.
[0014] Furthermore, the fluorine-containing monomer is prepared by the following steps: adding 1H,1H-perfluoro-1-hexanol and 3-N,N-dimethylaminomethyl acryloyl chloride into a reactor, heating and reacting until completion under the protection of an inhibitor, cooling, washing, drying and distilling to obtain the fluorine-containing monomer.
[0015] The highly hydrophobic polyacrylonitrile spinning stock solution of the present invention has a tertiary amine structure and a long-chain carbon fluorine structure in the copolymerized fluorine-containing monomer. On the one hand, the non-polar and multi-branched tertiary amine structure can give the polyacrylonitrile excellent hydrophobicity and improve the dispersibility of the prepared fiber, thereby increasing the number of pores on the fiber surface; on the other hand, the long-chain carbon fluorine structure can not only further improve the hydrophobicity of the polyacrylonitrile, but also significantly improve the chemical resistance of the material.
[0016] Furthermore, the mass ratio of the 1H,1H-perfluoro-1-hexanol to 3-N,N-dimethylaminomethyl acryloyl chloride is 2-2.5:1.
[0017] Furthermore, the polymerization inhibitor is selected from one of hydroquinone, p-methoxyphenol or 2,6-di-tert-butyl-p-cresol.
[0018] Furthermore, the reaction temperature is 40-70° C., and the reaction time is 8-16 hours.
[0019] Furthermore, the alkenyl silane is selected from one of allyltriethoxysilane, vinyltriacetylsilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane or γ-methacrylatepropyltrimethoxysilane.
[0020] The highly hydrophobic polyacrylonitrile spinning stock solution of the present invention has a copolymerized alkenyl silane monomer with a multi-branched silane structure. On the one hand, the multi-branched spatial structure can further improve the hydrophobicity of polyacrylonitrile; on the other hand, the silane structure can be evenly dispersed on the surface of the prepared fiber and cross-linked to form a stable network structure, which can not only improve the chemical stability of the fiber material, but also play a protective role in the friction process of the fiber material, improve its wear resistance, and further improve the service life.
[0021] Furthermore, the organic solvent is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.
[0022] Any of the above-mentioned methods for preparing highly hydrophobic polyacrylonitrile spinning stock solutions comprises the following steps: adding acrylonitrile, fluorine-containing monomers, alkenyl silanes, initiators and organic solvents into a reactor, heating the mixture to 50-70°C and reacting the mixture for 12-40 hours, and removing residual monomers and bubbles by reduced pressure to obtain the highly hydrophobic polyacrylonitrile spinning stock solution.
[0023] Furthermore, the initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile.
[0024] Furthermore, the molar ratio of acrylonitrile, fluorine-containing monomer and alkenyl silane is (25-30): (5-8): (3-5).
[0025] Beneficial effects:
[0026] (1) The highly hydrophobic polyacrylonitrile spinning solution provided by the present invention is prepared by copolymerizing acrylonitrile, fluorine-containing monomers and alkenyl silanes in an organic solution. The copolymerized fluorine-containing monomers and alkenyl silanes can significantly improve the chemical stability and wear resistance of the fiber material prepared from the polyacrylonitrile spinning solution. The tertiary amine, carbon fluorine and silane structures in the monomers can effectively change the hydrophobicity of the fiber material, making it have excellent hydrophobicity, and can be widely used in polyacrylonitrile fiber materials in the field of oil-water separation.
[0027] (2) The highly hydrophobic polyacrylonitrile spinning stock solution provided by the present invention has a polyacrylonitrile structure with good processability. After spinning, it can form a fiber material with good mechanical properties and weather resistance. It can not only replace wool as a textile, but also be made into a fiber membrane as a membrane material for oil-water separation.
[0028] (3) In the highly hydrophobic polyacrylonitrile spinning stock solution provided by the present invention, the copolymerized fluorine-containing monomer has a tertiary amine structure and a long-chain carbon fluorine structure. On the one hand, the non-polar and multi-branched tertiary amine structure can give polyacrylonitrile excellent hydrophobicity and improve the dispersibility of the prepared fibers, thereby increasing the number of pores on the fiber surface; on the other hand, the long-chain carbon fluorine structure can not only further improve the hydrophobicity of polyacrylonitrile, but also significantly improve the chemical resistance of the material.
[0029] (4) In the highly hydrophobic polyacrylonitrile spinning stock solution provided by the present invention, the copolymerized alkenyl silane monomer has a multi-branched silane structure. On the one hand, its multi-branched spatial structure can further improve the hydrophobicity of polyacrylonitrile; on the other hand, its silane structure can be evenly dispersed on the surface of the prepared fiber and cross-linked to form a stable network structure, which can not only improve the chemical stability of the fiber material, but also play a protective role in the friction process of the fiber material, thereby improving its wear resistance and further improving its service life.
[0030] (5) The highly hydrophobic polyacrylonitrile spinning stock solution provided by the present invention can simultaneously graft fluorine-containing monomers and alkenyl silane structures into polyacrylonitrile, so that the long-chain carbon fluorine structure and the silane structure can be uniformly distributed on the surface of the fiber material at the same time, which can make up for the defects in the spatial structure between each other, improve the density of the surface structure of the fiber material, and significantly improve the stability of the manufactured fiber material through the synergistic effect. DETAILED DESCRIPTION
[0031] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0032] The commercially available polyacrylonitrile spinning stock solution is obtained by mixing PAN fine powder purchased from Dongguan Zhangmutou Hengtai Plastic Raw Materials Business Department with N,N-dimethylformamide; the remaining reagents and equipment are conventional reagents and equipment in this technical field.
[0033] Preparation of fluorinated monomers
[0034] The fluorinated monomers were prepared by the following steps:
[0035] In a reactor, 2 g of 1H,1H-perfluoro-1-hexanol and 1 g of 3-N,N-dimethylaminomethyl acryloyl chloride were added, and the mixture was heated to 60° C. under the protection of 0.1 g of hydroquinone, and then reacted for 12 hours, cooled, washed, dried, and distilled to obtain the fluorine-containing monomer;
[0036] Mass spectrum data of fluorinated monomer: The product was analyzed by LC-MS, and the m / z of the product was 411.07 (100.0%), 412.10 (13.9%).
[0037] Example 1
[0038] The highly hydrophobic polyacrylonitrile spinning solution was prepared by the following steps:
[0039] In a closed reactor, 0.3 mol of acrylonitrile, 0.05 mol of a fluorine-containing monomer, 0.03 mol of allyltriethoxysilane, 0.3 g of azobisisobutyronitrile and 100 mL of N,N-dimethylformamide were added, and the temperature was raised to 70° C. and reacted for 24 hours. After the residual monomers and bubbles were removed by decompression, the highly hydrophobic polyacrylonitrile spinning solution was obtained.
[0040] Example 2
[0041] The method is basically the same as Example 1, except that the monomers and their contents are changed to 0.25 mol of acrylonitrile, 0.08 mol of fluorine-containing monomer and 0.04 mol of vinyl triacetyl silane.
[0042] Example 3
[0043] The process is basically the same as Example 1, except that the monomers and their contents are changed to 0.23 mol of acrylonitrile, 0.08 mol of fluorine-containing monomer and 0.05 mol of γ-methacrylatepropyltrimethoxysilane.
[0044] Comparative Example 1
[0045] Commercially available polyacrylonitrile spinning solution.
[0046] Comparative Example 2
[0047] The process is basically the same as in Example 1, except that the fluorine-containing monomer is replaced by an equal amount of acrylonitrile.
[0048] Comparative Example 3
[0049] The process is basically the same as Example 1, except that allyltriethoxysilane is replaced by an equal amount of vinylidene chloride.
[0050] Comparative Example 4
[0051] The method is basically the same as Example 1, except that the fluorine-containing monomer is replaced by an equal amount of acrylonitrile; and allyltriethoxysilane is replaced by an equal amount of vinylidene chloride.
[0052] Performance Testing
[0053] The products of Examples 1-3 and Comparative Examples 1-4 were respectively prepared into fibers of the same specifications through the steps of wet spinning, coagulation molding, water washing, heat drawing, drying, heat setting, etc., and the performance tests were carried out.
[0054] Tensile strength test: According to the test standard of GB / T 3362-2005 carbon fiber multifilament tensile performance test method, the tensile strength of the fibers obtained from the products of Examples 1-3 and Comparative Examples 1-4 was tested.
[0055] Acid resistance test: The fibers obtained from the products of Examples 1-3 and Comparative Examples 1-4 were immersed in a 25 wt % sulfuric acid aqueous solution for 240 hours, and the tensile strength of the fibers after immersion was tested again.
[0056] Alkali resistance test: The fibers obtained from the products of Examples 1-3 and Comparative Examples 1-4 were respectively immersed in a 10 wt % sodium hydroxide aqueous solution for 240 hours, and the tensile strength of the fibers after immersion was tested again.
[0057] Wear resistance test: According to the test method of GB / T1768-2006, the wear quality of the fibers obtained from the products of Examples 1-3 and Comparative Examples 1-4 was tested at 750g / 500r.
[0058] Hydrophobicity test: The water contact angles of the fibers obtained from the products of Examples 1-3 and Comparative Examples 1-4 were tested.
[0059] The test results are shown in the following table:
[0060]
[0061]
[0062] According to the comparison of the test results of Examples 1-3 with those of Comparative Example 1, it can be seen that the fiber material prepared from the highly hydrophobic polyacrylonitrile spinning solution provided by the present invention has excellent mechanical strength and stability, and strong hydrophobicity, and can be effectively used in the field of oil-water separation.
[0063] According to the comparison of the test results of Examples 1-3 and Comparative Examples 2-4, it can be seen that the highly hydrophobic polyacrylonitrile spinning solution provided by the present invention can significantly provide the mechanical strength, acid and alkali resistance and wear resistance of the prepared fiber material through the structure of its polymerized fluorine-containing monomer and alkenyl silane monomer, and can significantly improve the hydrophobic properties of the fiber material.
[0064] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly hydrophobic polyacrylonitrile spinning solution, characterized in that: The highly hydrophobic polyacrylonitrile spinning solution is prepared by copolymerizing acrylonitrile, a fluorine-containing monomer and alkenyl silane in an organic solution; The fluorine-containing monomer has a structure as shown in the following formula A:
2. The highly hydrophobic polyacrylonitrile spinning solution according to claim 1, characterized in that: The fluorine-containing monomer is prepared by the following steps: adding 1H,1H-perfluoro-1-hexanol and 3-N,N-dimethylaminomethyl acryloyl chloride into a reactor, heating to react until completion under the protection of an inhibitor, cooling, washing, drying and distilling to obtain the fluorine-containing monomer.
3. The highly hydrophobic polyacrylonitrile spinning solution according to claim 2, characterized in that: The mass ratio of the 1H,1H-perfluoro-1-hexanol to 3-N,N-dimethylaminomethyl acryloyl chloride is 2-2.5:
1.
4. The highly hydrophobic polyacrylonitrile spinning solution according to claim 2, characterized in that: The polymerization inhibitor is selected from one of hydroquinone, p-methoxyphenol or 2,6-di-tert-butyl-p-cresol.
5. The highly hydrophobic polyacrylonitrile spinning solution according to claim 2, characterized in that: The reaction temperature is 40-70° C., and the reaction time is 8-16 hours.
6. The highly hydrophobic polyacrylonitrile spinning solution according to claim 1, characterized in that: The alkenyl silane is selected from one of allyl triethoxy silane, vinyl triacetyl silane, vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane or γ-methacrylate propyl trimethoxy silane.
7. The highly hydrophobic polyacrylonitrile spinning solution according to claim 1, characterized in that: The organic solvent is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.
8. The method for preparing the highly hydrophobic polyacrylonitrile spinning solution according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: adding acrylonitrile, fluorine-containing monomer, alkenyl silane, initiator and organic solvent into a reactor, heating to 50-70°C and reacting for 12-40 hours, removing residual monomer and bubbles by decompression, and obtaining the highly hydrophobic polyacrylonitrile spinning stock solution.
9. The method for preparing highly hydrophobic polyacrylonitrile spinning solution according to claim 8, characterized in that: The initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile.
10. The method for preparing highly hydrophobic polyacrylonitrile spinning solution according to claim 8, characterized in that: The molar ratio of acrylonitrile, fluorine-containing monomer and alkenyl silane is (25-30): (5-8): (3-5).
Citation Information
Patent Citations
Spinning solution containing silicon acrylonitrile copolymer and preparation method thereof
CN102102235A
Preparation method and application of second monomer for acrylonitrile-based copolymer solid-solid phase change material
CN103965464A
Preparation method of nanofiber membrane material with convertible hydrophilicity and hydrophobicity
CN112323254A
Preparation method and application of polyacrylonitrile-based Janus film
CN118257067A
Water-repellent acrylonitrile fiber
JP1994248507A